2019
DOI: 10.1016/j.psyneuen.2018.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cerebrospinal fluid GABAergic neurosteroid levels and symptom severity in men with PTSD

Abstract: Allopregnanolone and pregnanolone (together termed allo + pregnan) are neurosteroid metabolites of proges-terone that equipotently facilitate the action of gamma-amino-butyric acid (GABA) at GABA A receptors. The adrenal steroid dehydroepiandrosterone (DHEA) allosterically antagonizes GABA A receptors and facilitates N-methyl-D-aspartate (NMDA) receptor function. In prior research, premenopausal women with posttraumatic stress disorder (PTSD) displayed low cerebrospinal fluid (CSF) levels of allo + pregnan [un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 61 publications
4
49
0
Order By: Relevance
“…While it is important that these findings will be confirmed also in blood and post-mortem brain of PTSD patients [101], this observation provides support to the involvement of the PPAR-allopregnanolone axis dysfunction in PTSD. Together with the findings that allopregnanolone has been found decreased in cerebrospinal fluid (CSF) and plasma of both male and female PTSD and MDD patients [95,[97][98][99]102], these clinical data provide a translational example with PTSD animal models [103].…”
Section: Mood Disordersmentioning
confidence: 73%
“…While it is important that these findings will be confirmed also in blood and post-mortem brain of PTSD patients [101], this observation provides support to the involvement of the PPAR-allopregnanolone axis dysfunction in PTSD. Together with the findings that allopregnanolone has been found decreased in cerebrospinal fluid (CSF) and plasma of both male and female PTSD and MDD patients [95,[97][98][99]102], these clinical data provide a translational example with PTSD animal models [103].…”
Section: Mood Disordersmentioning
confidence: 73%
“…It is interesting to note, that ALLO levels have been found to be decreased relative to controls in the CSF of women with chronic stress disorders, such as PTSD (75). A subsequent study from this group observed a negative correlation between CSF levels of total GABAergic neurosteroids levels (ALLO plus pregnanolone) and PTSD symptoms in men (76). This study also found an association between PTSD and reduced 5α-reductase mediated biosynthesis of ALLO in men, which is in contrast to the block at 3α-HSD previously observed in women with PTSD.…”
Section: The Role Of Neurosteroids In Memory Deficits Associated Withmentioning
confidence: 90%
“…The neurophysiological role of allopregnanolone in permitting the finetuning and regulation of the strength of GABA A receptors to agonists, positive allosteric modulators, and GABAmimetic agents, was also unveiled (Pinna et al 2000). By affecting GABA A receptors, allopregnanolone also regulates emotional animal behaviour in rodent stress models and humans with posttraumatic stress disorder and major unipolar depression (Rasmusson et al 2019;Pineles et al 2018).…”
Section: название разделаmentioning
confidence: 99%